IMPLEMENTASI NILAI-NILAI PANCASILA DALAM KEGIATAN KEPRAMUKAAN - Kristiono, Natal; Wiratomo, Giri Harto; Alfira, Hansa Nuha (Program Studi IPS Universitas Negeri Semarang Kampus Sekaran, Gunungpati, Semarang, 2019)
This study aims to find out about: (1) the implementation of the scout program activities in Madrasah Aliyah Al Asror (2) the role of scouts in implementing Pancasila values ??in Madrasah Aliyah Al Asror (3) Factors that support and hinder the implementation of scout education in the implementation of scout values the value of Pancasila in Madrasah Aliyah Al Asror. This type of research is a qualitative study, the findings are not obtained through statistical procedures or quantification. The informant in this study was the scoutmaster of Madrasah Aliyah Al Asror. Data collection techniques used were observation, interviews and documentation. The results of this study indicate that: (1) the implementation of the scout program in Madrasah Aliyah Al Asror has two types of scout activities, namely outdor and indor. To outdor with the existence of PBB (Line Regulation Line) and explore nature. As for indor with material and games in the room. (2) The application of the divine value can be seen from the obedience of members of scouts in practicing the teachings of Religion. The application of human values ??can be seen from the love between Scout members. Application of the value of unity seems to be carried out activities always prioritize to foster a sense of togetherness. The application of popular values ??can be seen from the preservation of democracy in scouting activities. The value of Justice can be seen from the tolerance level of Scout members. (3) Supporting factors for the implementation of Pancasila values ??in scouting activities are influenced by several factors, including having a program, providing infrastructure, and supervising and guiding by a scoutmaster. The inhibiting factor of the implementation of Pancasila values ??is derived from 2 factors, namely individual factors and supporting environment.   Penelitian ini bertujuan untuk mengetahui tentang: (1) pelaksanaan program kegiatan pramuka di Madrasah Aliyah Al Asror (2) peran pramuka dalam mengimplementasikan nilai-nilai Pancasila di Madrasah Aliyah Al Asror (3) Faktor yang mendukung dan menghambat pelaksanaan pendidikan pramuka dalam implementasi nilai-nilai Pancasila di Madrasah Aliyah Al Asror. Jenis penelitian ini adalah penelitian kualitatif, yaitu hasil temuannya tidak diperoleh melalui prosedur statistik atau cara kuantifikasi. Informan dalam penelitian ini adalah pembina pramuka Madrasah Aliyah Al Asror. Teknik pengumpulan data yang digunakan adalah observasi, wawancara serta dokumentasi. Hasil penelitian ini menunjukkan bahwa: (1) pelaksanaan program kegiatan pramuka di Madrasah Aliyah Al Asror memiliki dua jenis kegiatan pramuka, yaitu outdor dan indor. Untuk outdor dengan adanya PBB (Peraturan Baris Berbaris) dan menyusuri alam. Sedangkan untuk indor dengan materi dan permainan didalam ruangan. (2) Penerapan nilai ketuhanan tampak terlihat dari ketaatan anggota pramuka dalam mengamalkan ajaran-ajaran Agama. Penerapan nilai kemanusiaan tampak dari rasa kasih sayang antar anggota Pramuka. Penerapan nilai persatuan tampak kegiatan yang dilakukan selalu mengedepankan untuk memupuk rasa kebersamaan. Penerapan nilai kerakyatan tampak dari terjaganya demokrasi dalam kegiatan kepramukaan. Nilai Keadilan tampak dari tingkat toleransi anggota Pramuka. (3) Faktor pendukung implementasi nilai-nilai Pancasila dalam kegiatan pramuka dipengaruhi oleh beberapa faktor, di antaranya mempunyai program, menyediakan sarana prasarana, dan pengawasan dan pembinaan oleh pembina pramuka. Faktor penghambat implementasi nilai-nilai Pancasila bersumber dari dua  faktor, yakni faktor individu dan lingkungan penunjang.